PENIPUAN KOMPUTER PADA SISTEM INFORMASI AKUNTANSI: TANTANGAN KEAMANAN DI PERUSAHAAN BERBASIS TEKNOLOGI - Dargio Akbari Sutanto; Shafiq Hamam Adingga; Fahri Reza Ramadhan; Tegar Ryamizard (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This article discusses the security issues faced by technology-driven businesses in the field of Accounting Information Systems (AIS). The use of AIS in the digital age helps companies manage financial data more effectively, but it also brings risks, such as cybersecurity threats and computer fraud. This study, conducted using a qualitative method in the form of a literature review, aims to identify the types of computer fraud that commonly occur in AIS and the challenges companies face in preventing them. Additionally, this paper provides strategic recommendations for enhancing AIS security, including implementing the latest security technologies, strengthening internal controls, and educating employees about cybersecurity threats. By implementing these measures, it is hoped that businesses can reduce their risk of fraud and maintain the accuracy of their financial data.